The Digitalisation of Anti-Corruption in Brazil: Scandals, Reforms, and Innovation - Odilla, Fernanda (Routledge Corruption and Anti-Corruption Studies, 2025)
This book investigates how digital technologies, such as social media and artificial intelligence, can contribute to combatting corruption in Brazil. Brazil, with its long history of scandals and abundant empirical data on digital media usage, serves as a perfect case study to trace the development of bottom-up and top-down digital anti-corruption technologies and their main features. This book highlights the connections between anti-corruption reforms and the rapid implementation of innovative solutions, primarily developed by tech-savvy public officials and citizens committed to anti-corruption efforts. The book draws on interviews with experts, activists and civil servants, as well as open-source materials and social media data to identify key actors, their practices, challenges and limitations of anti-corruption technologies. The result is a thorough analysis of the process of digitalisation of anti-corruption in Brazil, with a theoretical framework which can also be applied to other countries. The book introduces the concept of “integrity techies” to encompass social and political actors who develop and facilitate anti-corruption technologies, and discusses different outcomes and issues associated with digital innovation in anti-corruption. This book will be a key resource for students, researchers and practitioners interested in technologies and development in Brazil and Latin America, as well as corruption and anti-corruption studies more broadly.